الروابط والعوامل الحجاجيّة في قصيدة (هذه قمّة الفتوّة) لمحمد العيد آل خليفة - عبابة, البشير (جامعة الوادي - University of Eloued, 2021)
ملخص: تتناول هذه الدراسة الروابط والعوامل الحجاجيّة التي وردت في قصيدة (هذه قمّة الفتوّة) لمحمد العيد آل خليفة؛ إذ تبيّن مختلف الأدوات الحجاجيّة التي وظّفها الشاعر هنا كي يوصل فكرته إلى الشباب ويقنعهم بما يودّ إقناعهم به, وتوجيه خطابه الشعريّ الوجهة التي يريدها, لاسيما أنّ هذه الفترة تعدّ قمّة العطاء البشريّ في مختلف المجالات, وتحتاج إلى توجيهٍ من طرف الأكثر خِبْرة في الحياة, فجاءت هذه الأدوات الحجاجيّة متنوّعة في القصيدة, فأضْفت عليها تماسكا جليّا ومبرزة الحجج ونتائجها. Abstract: This study deals with connectors and argumentative factors mentioned in the poem (This is the Summit of the Youth) written by Mohammed Al-Eid Al-Khalifa. It shows the various argumentative tools that the poet employed here in order to communicate his idea to the youth and convince them of what he wants to convince them of, and direct his poetic discourse the direction he wants, especially since this period is the pinnacle of human giving in various fields, and it needs guidance from the most experienced in life. These argumentative tools are diverse in the poem, adding to it a clear coherence and highlighting the arguments and their results.
مقال
Keywords: الحِجاج، الروابط، العوامل، اللغوية، آل خليفة; Argumentation, Connectors, Factors, Linguistics, Al- Khalifa